BIBLIOMETRIC ANALYSIS OF PATIENT OUTCOMES AND SATISFACTION IN ROBOTIC-ASSISTED HIP AND KNEE JOINT REPLACEMENT SURGERY - Bintang Soetjahjo; Asep Santoso; Grendi Mercy; Denny Adriansyah; Agiona Angeline; Daffa Sadewa (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Robotic-assisted hip and knee arthroplasty has gained popularity in orthopedic surgery due to its precision, faster recovery, and improved alignment, potentially enhancing patient outcomes. Despite mixed and heterogeneous evidence, the demand for these procedures continues to rise. Therefore, bibliometric analysis is essential to direct research towards patient satisfaction and generate more reliable and significant evidence proving the true benefits of robotic surgery for patients, rather than merely technical success. This study employed bibliometric analysis to explore trends and evaluate publications on patient outcomes and satisfaction in robotic-assisted hip and knee surgery using the Scopus database. The analysis identified core concepts, trends, and research connections, providing insights into emerging areas in the field. The bibliometric analysis of 324 documents from 2007 to 2025 reveals a significant increase in research, focusing on surgical precision, rehabilitation, and long-term effectiveness. While countries like the US, UK, and China are leading contributors, there is a notable lack of similar research in ASEAN countries, particularly Indonesia. Future research should address gaps in areas like surgical revision, patient perception, and improving patient-reported outcomes.